Patch Testing in Allergic Contact Dermatitis - Sharma, Rashmi; Shrestha, Dwarika Prasad (Journal of Nepal Health Research Council, 2024)
Background: Allergic contact dermatitis is one of the most common forms of skin diseases that require medical intervention. Appropriate detection of allergens by patch test and accurate avoidance of them is the key to management. The objective of this study is to determine the types and frequency of allergens responsible for Allergic contact dermatitis in a tertiary hospital of Nepal. Methods: Altogether 120 patients with Allergic contact dermatitis were enrolled in the study. Patch test was performed to find out the most common inciting allergen, utilizing the Indian Standard Series of allergens approved by The Contact and Occupational Dermatoses Forum of India. Results were read at 48 and 96 hours. Grading of the reactions was done based on the criteria of the International Contact Dermatitis Research Group. Pattern of reactivity of different allergens was assessed.Results: Of all the patients, 63 (53%) showed positivity to at least one allergen. Nickel sulfate was the most frequent sensitizing agent in 22 (18%) cases, followed by Fragrance mix in 11(9%) and Paraphenylenediamine in 7 (6%) cases. Out of all positive results, Grade 1 positivity was seen in 44 (51%), Grade 2 positivity in 41(47%) and only 2 (2%) cases showed Grade 3 positivity. Mercaptobenzothiazole, Balsam of Peru, Nitrofurazone and Wool Alcohol did not show positive results in any of our patients.Conclusions: Patch testing helps in the treatment, long term remission, and patient counseling for prevention. Larger scale studies are required to know the sensitivity to allergens in Nepalese population.Keywords: Allergens; allergic contact dermatitis; nickel; patch test.